(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Lipomas are adipose mesenchymal neoplasms. The oral cavity is not commonly affected. representing about0.5% to 5% of all benign oral tumors. The clinical presentation is typically as an asymptomatic yellowish mass.The overlying epithelium is intact and superficial blood vessels are usually evident over the tumour. Although benign in nature their progressive growth may cause interference with speech and mastication due to tumour’s dimension. The present report shows the case of a 52-year old male who presented with a large intraoral lipoma with extension to the right submandibular region. Bangladesh J Otorhinolaryngol; April 2016; 22(1): 58-61